Concentric compressive behavior of hybrid concrete–Stainless Steel Double-Skin Tubular Columns incorporating High Performance Concretes. (February 2021) - Hamoda, Ahmed; Abdelazeem, Fathi; Emara, Mohamed
Abstract: This paper investigates experimentally and numerically concentric compressive behavior of hybrid concrete–Stainless Steel (SS) Double-Skin Tubular Columns (DSTCs) employing High Performance Concretes (HPCs). DSTCs can be prefabricated using outer-and-inner double tubes positioned concentrically sandwiching the concrete core in-between. However, the ordinary steel tubes beside the poor mechanical properties of Normal Concrete (NC) may not be appropriate for the environmental attack. This research proposes employing two durable SS tubes sandwiching HPCs in-between to gain satisfied performance. Beside NC, three types of HPCs were suggested: Engineered-Cementitious Composites (ECC), High-Strength Fiber-Reinforced Concrete (HSFRC) and High-Strength Concrete (HSC). Forty specimens were tested experimentally under axial monotonic compressive loading up to failure. The main variables were: void ratio created by inner tube, concrete core type and vertical stiffeners embedded in the concrete core. Parallel to those implemented experimentally, nonlinear three-dimensional Finite Element Models (FEMs) were set-up, executed and validated against experimental outcomes generating an accepted model with about 6% error. Results revealed that the studied parameters could significantly enhance the behavior in terms of load–displacement response, elastic/plastic appearance, ultimate capacity, and capturing ductile failure mode. Finally, both experimental and numerical results were extended deriving new formula could estimate the ultimate capacity with difference about 12%. Highlights: Forty DSTCs were tested under axial monotonic compressive loading up to failure. Confining concrete with SS tubes enhanced elastic–plastic behavior of DSTCs. Embedded steel bars or SS stiffeners can improve the ultimate capacity of DSTCs. Concrete type together with vertical stiffeners affected the failure mode of DSTCs. New formula predicting the ultimate capacity of DSTCs were proposed.